The Prince Warriors and the Swords of Rhema - Book 3 - Shirer, Priscilla Evans; Detwiler, Gina (Nashville, Tennessee : B&H Publishing Group, 2017)
In the third book in The Prince Warriors trilogy, the Prince Warriors must align to face their greatest threat and learn the power of the swords of Rhema.
Keywords: Imaginary places -- Juvenile fiction; Spiritual warfare -- Juvenile fiction; Imaginary places -- Juvenile fiction; Spiritual warfare -- Juvenile fiction; Fantasy; Fantasy fiction; Religious fiction; Action and adventure fiction